Bronchopulmonary Dysplasia - Kakoo Brioso, Estela (2023)
INTRODUCTION: Bronchopulmonary dysplasia (BPD) is the most common complication associated with extreme prematurity. Although several criteria defining severity were developed over time, there are a few studies describing the differences in BPD phenotype and neonatal morbidities and complications between severity groups. We aimed to describe these differences in BPD patients of a neonatal intensive care unit (NICU). METHODS: We conducted an observational retrospective cohort study through a medical record review over a five-year period. Participants were newborns admitted to an NICU who were diagnosed with BPD. We performed a descriptive statistical analysis of gestational complications and the use of antenatal corticosteroid therapy, birth-related data, and complications throughout the NICU stay, as well as the respiratory support used. We also compared different severity groups across these variables. The patients were divided into severe and non-severe BPD using the severity criteria of the 2001 NICHD/NHLBI/ORD consensus workshop. RESULTS: A total of 101 newborns with BPD participated in the study and 73 had data on BPD severity. The median gestational age was 27 weeks, ranging from 23 to 32 weeks. Of these 73 newborns, 36 had mild BPD (49.3%), 10 had moderate BPD (13.7%), and 27 had severe BPD (37.0%). When comparing severe and non-severe BPD, we found that extreme prematurity, extremely low birth weight, and small size for gestational age were more frequent in the severe BPD group (p-value=0.012, p-value<0.001, and p-value=0.012, respectively). Infants with severe BPD had a longer duration of invasive ventilation than those with mild or moderate BPD (p-value<0.001). Late sepsis, necrotizing enterocolitis, severe brain injury, and retinopathy of prematurity were more frequent in severe BPD (p-value=0.017, p-value=0.045, p-value=0.033, p-value=0.003, respectively). DISCUSSION: Previously published evidence describing causal links between BPD development and comorbidities exists but data on their impact on BPD severity are scarce. In our study, severe BPD seemed to be associated with a higher frequency of comorbidities and complications. Further studies are needed to ascertain the impact of each morbidity on the severity of BPD and if measures to prevent them could lead to potentially milder BPD disease.